7h+4=3-2h

Simple and best practice solution for 7h+4=3-2h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7h+4=3-2h equation:


Simplifying
7h + 4 = 3 + -2h

Reorder the terms:
4 + 7h = 3 + -2h

Solving
4 + 7h = 3 + -2h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '2h' to each side of the equation.
4 + 7h + 2h = 3 + -2h + 2h

Combine like terms: 7h + 2h = 9h
4 + 9h = 3 + -2h + 2h

Combine like terms: -2h + 2h = 0
4 + 9h = 3 + 0
4 + 9h = 3

Add '-4' to each side of the equation.
4 + -4 + 9h = 3 + -4

Combine like terms: 4 + -4 = 0
0 + 9h = 3 + -4
9h = 3 + -4

Combine like terms: 3 + -4 = -1
9h = -1

Divide each side by '9'.
h = -0.1111111111

Simplifying
h = -0.1111111111

See similar equations:

| 2+r=-11 | | X+3=4x+12 | | K+11=13 | | 14=-2/3v | | -6a-12=14 | | -25=20t+5t^2 | | 2b+3b+6=21 | | 2-8/-2-3--12/-6*-2 | | -6-v=-22 | | 5+2r+6=9 | | 3x+4+6x=14x | | 28=7+4(y+8) | | 6h+h=5 | | T/5-9= | | 2(x+10)=58 | | 17=y^3+4y+1 | | 6+5(m+1)=-26 | | x+x(.08)=539.99 | | 3(m+5)+1=2(m+1)-9 | | -14b+6b+7+-2b=1+5b | | xyz=kt | | (x+5)(y+z)=6 | | -3v+9+8v=2v | | -7/-2/5 | | 23+4z=83 | | -14+6b+-2b=q | | 0=8+3n^7+2n^6+9n^7-8n^6+4 | | Z-9z=9 | | 2x+y=7fory | | 9x-(5x+4)=2x-32 | | x^2+34x+275= | | 2(y-6)/3=-2y |

Equations solver categories